Monitoring Results of a Small Scale CHCP System - Mendes, J. Farinha (2010)
A small scale trigeneration system for combined heat, cold and power production was developed and installed at the Laboratório Nacional de Energia e Geologia, I.P. campus in Lisbon, Portugal. This system is one of the twelve experimental trigeneration systems being developed and tested across Europe within the PolySMART project. The CHCP system main constituents are a purpose made CHP prototype with an estimated 27kW maximum heat capacity and 9,6kW maximum electrical capacity and a TDC prototype with 8kW cooling power. The hydraulic scheme is presented and briefly analyzed. The data obtained during the monitoring of the system during heat and cold seasons is presented and analyzed for the global system. Main components behavior is analyzed with regard of their real performance when installed on a CHCP system.